The Research of Secondary Arc Spectrum Characteristics on UHV - Baina He; Yunwei Zhao (Institute of Advanced Engineering and Science, 2012)
On UHV power transmission lines, when single-phase ground fault happen, it will appear secondary arc on lines, the existence of secondary arc impact on the stable operation of system. The effectiveness of single-pole autoreclosure (SPAR) in maintaining power system stability is largely determined by the speed with which secondary arc extinction, and hence autoreclosure, can be achieved. The paper adopts total harmonic distortion (THD) to judge the status of arc. First, the simulation model of secondary arc is established by ATP software. Then, faulted phase voltage and secondary arc are simulated in different close angle. Last, spectrum characteristics and harmonic content of faulted phase voltage and current are analyzed in different close angle, at the same time, THD of non-faulted phase is also analyzed by Fourier algorithm. Through the fault phase voltage and current simulation and Fourier analysis, which comes to the conclusion that at the peak in the power supply voltage secondary arc is the most difficult to extinguish and the harm to insulation is the greatest. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1411